ʿAḇdīšōʿ of Gazarta: Patriarch, Poet and Scribe : East Syriac Poetry and Manuscript Culture of the Ottoman Period - Pritula, Anton D., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
ʿAḇdīšōʿ of Gazarta: Patriarch, Poet and Scribe focuses on the literary legacy of the prominent East Syrian poet and churchman who lived in the 16th century. The role of ʿAḇdīšōʿ of Gazarta for East Syriac ecclesiastical poetry is significant. He was the second patriarch of the Chaldean Church and the founder of its literary tradition. This book also explores for the first time the manuscript autographs of ʿAḇdīšōʿ of Gazarta, previously unavailable to scholars. In addition, many of this author's poetic texts are critically published and translated for the first time.